CORRELATION OF THE PORTUGUESE STOCK MARKET WITH MAJOR GLOBAL CAPITAL MARKETS - Couto, Gualter; Pimentel, Pedro; Faria, Ricardo (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper, we will analyse the increase of correlations in the market during periods of crisis, given its importance to the management and optimization of the portfolio, and especially for risk diversification in portfolio management. An evaluation of the level of correlation between the stock markets is important for several reasons. First, it enables to evaluate changes in the patterns of correlation, and thus to make the proper adjustments in portfolios’ investment. Second, policy makers are also interested in these correlations because of its implications for the stability of the financial system. The correlation coefficients are biased measures of dependence when markets become more volatile. This paper explores the correlation of the Portuguese capital markets with the Asian, American, European and Latin American Spanish stock markets. To this end, we used the PSI-20 index, Nikkei 225, NASDAQ, S&P 500, Euronext 100 and Ibex-35. Our analysis results show that the correlation does exist as a phenomenon during financial crises (Bear Market), reducing the benefits of portfolio diversification when most needed. Moreover, we believe that correlations have increased between the markets in recent years.